Development of Animated Video Media Using Powtoon Application to Improve the Fourth-Grade Elementary Students’ Motivation in Learning - Hutapea, Indah Romasari; Silaban, Patri Janson; Sari H.S, Dyan Wulan; Raja, Bogor Lumban; Mahulae, Saut (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper examines the development, feasibility, and response of students about animated video media using the Powtoon application in order to increase students’ learning motivation in theme 8 of My Living Area on Subtheme 1 of My Living Environment Learning 1 in Class IV SD ST. Antonius Bangun Mulia Medan. The research is a research and development using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects are four validators, namely one validator of learning media design experts, two experts in learning media materials, and one education practitioner who is carried out by class teachers. The sample consists of 30 students. Data collection techniques are tests, questionnaires, and documentation. Based on data analysis, it is concluded that animated video media using the Powtoon application to increase students’ motivation in learning result is "Very Feasible", which was used with details of the average scores obtained by media and material experts with a final score at 100%, the media at 87.98% and material experts at 100% with the same category. In terms of practicality, the teacher's average score is 100% with the category "Very Feasible". The results of the question reliability are 0.900 with a very strong category and the results of the questionnaire reliability were 0.878 with a very strong category. Results of the coefficient Sis at 0.855 so it can be concluded that there is a significant effect. At the last stage, the summary model result, which is proven by the value of R Square or Coefficient of Determination (KD), is 73.1% so it can be concluded that Ho isrejected, which means that there is an improvement in learning motivation after students use the animated video media Powtoon application in class IV SD ST. Antonius Bangun Mulia Medan.